Drug-loaded bispecific T cell nanoengager overcomes T cell exhaustion for potent cancer immunotherapy - Jinjin Wang; Xisha Huang; Qiangqiang Shi; Kelsey L. Swingle; Alex G. Hamilton; Ningqiang Gong; Michael J. Mitchell (Proceedings of the National Academy of Sciences, 2025)
Bispecific T cell engager (BiTE) therapeutics that link T cells and tumor cells to induce tumor cell lysis have demonstrated great success in the clinic for the treatment of many cancers. However, T cell exhaustion in the tumor microenvironment leads to tumor cell escape and BiTE therapy resistance. Herein, we developed a drug-loaded bispecific T cell nanoengager (NanoBiTE) to overcome this obstacle. NanoBiTE is composed of a mesoporous silica nanoparticle encapsulating the adenosine A2A receptor antagonist PBF-509 as a core, with a lipid layer surface coating as a shell and modification with anti-CD19 and anti-CD3 antibodies for tumor and T cell binding, respectively. Like the traditional BiTE blinatumomab, NanoBiTE can engage T cells with CD19 + tumor cells to promote tumor cell lysis. However, unlike blinatumomab, which tends to induce T cell exhaustion, we showed that the release of PBF-509 from NanoBiTE suppressed the A2AR pathway and substantially improved tumor cell killing induced by NanoBiTE. Moreover, NanoBiTE treatment led to substantially reduced tumor burden in vivo in a humanized mouse model. Our results demonstrate that NanoBiTE is a safe and potent bispecific therapy that can also reduce T cell exhaustion for cancer immunotherapy.